In Vitro Antimicrobial Efficacy of Leaves Extracts of Bauhinia variegata - Sharma, R.N.; Saxena, V.K. (Asian Journal of Chemistry, 2010)
The methanolic extract obtained from the leaves of Bauhinia variegata has been tested for their antimicrobial activity against Bacillus anthracis, Proteus vulgaris, Escherichia coli and Streptococcus agalacties and antifungal activity against various fungi, Aspergillus fumigatus and Aspergillus niger.